Electroconvulsive therapy selectively enhances amyloid β 1-42 in the cerebrospinal fluid of patients with major depression: A prospective pilot study - Kranaster, Laura; Janke, Christoph; Alonso, Angelika; Hoyer, Carolin; Frölich, Lutz; Sartorius, Alexander (European neuropsychopharmacology, 2016)
A complex interplay between β-amyloid (Aβ), Alzheimer׳s disease (AD) and major depression disorder (MDD) suggests that patients with MDD have an altered cerebral Aβ metabolism and an increased risk of developing AD. In order to elucidate the relationship between antidepressant treatment and Aβ metabolism in humans, we performed a study on Aβ peptides in the cerebrospinal fluid (CSF) in patients with MDD during electroconvulsive therapy (ECT) as an effective antidepressant treatment. We measured the levels of Aβ1-42, Aβ1-40 and of tau proteins in the CSF in 12 patients with MDD before and after a course of ECT. Aβ1-42 was significantly elevated after the ECT treatment compared to baseline, whereas no difference was found for other peptides and proteins such as Aβ1-40, Aβ ratio, total tau protein or its phosphorylated form. The most salient finding was, that the increase of Aβ1-42 after ECT was found in all patients with clinical response to the treatment, but not in those who did not respond. The number of ECT sessions of each responding patient correlated with the increase of Aβ1-42 in the CSF. Our data point towards to a specific antidepressant mechanism which is not based on a general increase of Aβ, but seems to involve merely Aβ1-42, the isoform with highest amyloidogenic potential. We present the first study in humans demonstrating an isolated mobilization of Aβ1-42 in the CSF of patients with depression who respond to an ECT treatment.